Influence of Surface Preparation on XRD Peak Parameters and Residual Stress Measurements - Salvetr, Pavel; Gokhman, Aleksandr; Drahokoupil, Jan (Manufacturing Technology Journal, 2025)
X-ray diffraction (XRD) is an analytical technique used to investigate the crystal structure properties of materials. However, the accuracy of XRD measurements can be significantly affected by the sam-ple's surface preparation. This study evaluates the impact of various surface preparation methods on the diffraction peak characteristics, phase composition, and residual stress analysis of two metallic materials: very low alloyed iron-based alloy labelled as pure iron and hardened 54SiCr6 steel. Various final steps of metalographic preparation of the surface for XRD were used, including mechanical grinding with coarse (P120) and fine (P1200) sandpapers, polishing with OPS colloidal silica, chemical etching in hot hydrochloric acid, and electrolytic etching. The results show that surface conditions influence more on the full width at half maximum (FWHM) than the intensity of diffraction peaks. Furthermore, the annealed pure iron sample (with low hardness) exhibited a more pronounced sensi-tivity to surface preparation compared to hardened 54SiCr6 steel, with its martensitic microstructure. Residual stress analysis using the sin2ψ method further revealed that mechanical grinding induces substantial compressive residual stress while polishing and etching methods produce nearly neutral or slightly tensile residual stresses. These findings highlight the importance of consistent and appropri-ate surface preparation methods for reliable XRD analysis.
Keywords: XRD diffraction; Peak characteristics; Residual stress; Surface preparation; Dislocation density